Obestatin does not modify weight and nutritional behaviour but is associated with metabolic syndrome in old women. (25th March 2013) - Mora, Mireia; Granada, Maria L.; Roca, Maria; Palomera, Elisabet; Puig, Rocio; Serra‐Prat, Mateu; Puig‐Domingo, Manel
Summary Objective Ghrelin and obestatin have apparent opposite orexigenic and anorexigenic effects, although the latter has not been firmly demonstrated in humans. So far, little data have been reported in relation to its potential association with metabolic syndrome (MS). The objective was to study obestatin concentrations in relation to nutritional parameters and eating behaviours in old women. Design, Patients and Measurements Prospective study; a total of 110 women (age: 76·93 ± 6·32) from the Mataró Ageing Study were included. Individuals were characterized by anthropometric variables, lipids, glucose, blood pressure, MS components (Adult Treatment Panel III criteria), anorexia and nutritional status by Mini Nutritional Assessment Short Form (MNA‐SF) and re‐evaluated at 2‐year follow‐up. Obestatin was measured by IRMA. Results 58·2% of the subjects had MS; at 2‐year follow‐up 24·1% had a weight loss >5%, 7·2% >10%, and 26·4% changed their MNA‐SF score to risk of malnutrition category. Anorexia was present in 38·4%. Obestatin levels were not related to either change of weight, MNA‐SF or anorexia, but a positive correlation was found with the absolute difference between basal and 2‐year waist circumference (WC) (r = 0·429; P < 0·001) and relative difference between basal and 2‐year WC (r = 0·420; P < 0·001); both remained significant after adjusting for age and body mass index. When obestatin was divided into quartiles, a significant lineal trend was observed in relation to WC (P = 0·049), absolute and relative difference between basal and 2‐year WC (both P < 0·001). Obestatin was associated with glucose impairment (69·0% in 4th quartile vs 47·5% in 1st to 3rd, P = 0·047; after adjustment, P = 0·098) and MS (77·8% in 4th vs 51·3% in 1st to 3rd, P = 0·017; after adjustment, P = 0·046, OR 2·90 (1·02–8·25) 4th vs 1st to 3rd). Conclusions Obestatin is elevated in aged women bearing MS but is otherwise not associated with other nutritional parameters, weight loss or anorexia.